Formation of Polymeric Particles by Direct Polymerization on the Surface of a Supramolecular Template. Issue 36 (1st June 2018) - Li, Mao; Zellermann, Elio; Schmuck, Carsten
Abstract: Formation of polymeric materials on the surface of supramolecular assemblies is rather challenging because of the often weak noncovalent interactions between the self‐assembled template and the monomers before polymerization. We herein show that the introduction of a supramolecular anion recognition motif, the guanidiniocarbonyl pyrrole cation (GCP), into a short Fmoc‐dipeptide1 leads to self‐assembled spherical nanoparticles in aqueous solution. Negatively charged diacetylene monomers can be attached onto the surface of these nanoparticles, which, after UV polymerization, leads to the formation of a polymer shell around the self‐assembled template. The hybrid supramolecular and polymeric nanoparticles demonstrate intriguing thermal hysteresis phenomena. The template nanoparticles could be disassembled upon treatment with organic base, which cleaved the Fmoc moiety on1 . This strategy thus showed that a supramolecular anion recognition motif allows the post‐assembly formation of polymeric nanomaterials from anionic monomers around a cationic self‐assembled template. Abstract : Assembly in a shell : Self‐assembled aggregates can serve as a template for the formation of a polymer shell provided that the interaction between template and monomer are sufficiently strong. The assembly inside the polymeric shell exhibited thermal hysteresis in the assembly–disassembly cycle.